The perceived psychological well-being of LGBTQ individuals in Malaysia - Jaffer, Usman; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Ahmad H Osman, Rahmah; Abdul Malik, Aleeya Aesya; Alba, Mohd Shahril Aidil; Ab Rahim, Muhammad Akmal Hakim; Hasbi, Dinah Jazmina; Mohamad, Mardhiyah (Global Academic Excellence (M) Sdn Bhd, 2023)
This study explores the psychological well-being of lesbian, gay, bisexual, and transgender (LGBTQ) individuals in Malaysia, focusing on their experiences of identity formation, societal understanding, and the impact of prevailing attitudes on their mental health. Through qualitative methods, including in-depth interviews with nine participants from the LGBTQ community in Kuantan, Pahang, this research delves into the personal narratives of two lesbians, two gay individuals, two bisexuals, and three transgender persons, to understand the complexities of living as an LGBTQ individual in a society marked by religious and legal considerations. .The findings reveal that participants recognized their LGBTQ identity during adolescence, often navigating societal expectations discreetly to avoid backlash. Despite challenges, participants demonstrated resilience and found support within familial and community networks. Notably, the study highlights a shift towards greater understanding of LGBTQ individuals in Malaysia, potentially reducing instances of psychological distress within the community. This research underscores the importance of supportive environments and the need for culturally competent mental health care for LGBTQ individuals. It also calls for further studies to include broader societal perspectives and professional insights to enrich the discourse on LGBTQ mental well-being. This study contributes valuable insights into the evolving landscape of LGBTQ perceptions and the factors influencing the psychological health of LGBTQ individuals in Malaysia.